Severe mucosal leishmaniasis with torpid and fatal evolution - Jesús Rojas Jaimes (Clinical Case Reports, 2022)
Abstract Mucosal leishmaniasis is a clinical condition that is difficult to diagnose and treat and usually precedes a cutaneous leishmaniasis condition with a long latency period as observed in our study of a patient who experienced a torpid evolution in 9 months, caused by having had cutaneous leishmaniasis on the neck without therapeutic treatment, although with ulcer closure 18 years earlier, incomplete treatment with antimonials and amphotericin B, with the destruction of the eyeball, a large area of necrosis on the face and nasal bone exposure. Additionally, the patient had chronic anemia (9.4 g/dl), lymphopenia and neutrophilia (lymphocytes 13.1%, neutrophils 84.4%), and co‐infections by fungi (yeasts and hyphae) and Gram‐negative bacteria (multidrug‐resistant Proteus mirabilis and Escherichia coli) leading to sepsis and subsequent death of the patient.